Ways to integrate artificial intelligence technologies into training programs for government and municipal employees - Bidzhiev, A. O.; Filimoniuk, L. A. (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. The conceptual change in the requirements to the professional competencies of public and municipal employees, consisting in the need to expand their knowledge, skills and abilities in the field of digital technologies and artificial intelligence technologies, which can significantly improve the efficiency and responsiveness of managerial decisions and public and municipal services, determines the need to integrate artificial intelligence technologies into training programs for public servants. Goal. The study aims to identify possible solutions to common problems of integrating artificial intelligence technologies into educational programs for state and municipal employees. Materials and methods. The study is based on the analysis of probable algorithms of actions of higher education institutions when faced with the most common problems of modernisation of training programs in terms of implementation of artificial intelligence technologies in them. Results and discussion. According to the results of the work, possible ways of solving the problems of integrating artificial intelligence technologies into training programs for state and municipal employees were identified, the advantages of these approaches were revealed and step-by-step algorithms of actions of higher education institutions in the application of the considered approaches were drawn up. Conclusion. According to the results of the study, the most common problems of integrating AI technologies into training programs are the shortage of qualified personnel, the lack of modern technical infrastructure and the low level of development of the relevant regulatory and legal framework – can be solved through large-scale cooperation with relevant companies, the creation of virtual laboratories using cloud platforms, as well as the formation of information and analytical systems containing auxiliary technologiesAt the same time, the actions of educational institutions within the framework of each approach require advance planning and should be carried out according to certain sequential algorithms.